Le Goût en Héritage : Exploration des transformations alimentaires dans quelques familles montréalaises - Jourdan, Christine; Poirier, Sylvain (Anthropologica, 2012)
This article presents the first results of a project studying changes in food ideologies and practices in Montreal, focusing on five families of the middle class over three genera tions. Its goal is to analyze the continuities, discontinuities and transformations that affect family food cultures over time. This analysis takes into account the main social and economic chang es that work to drive food ideologies and practices.